Effects of Tenofovir Disoproxil Fumarate in Hepatitis B e Antigen-Positive Patients With Normal Levels of Alanine Aminotransferase and High Levels of Hepatitis B Virus DNA - Chan, Henry L.Y.; Chan, Chi Kuen; Hui, Aric Josun; Chan, Sing; Poordad, Fred; Chang, Ting-Tsung; Mathurin, Philippe; Flaherty, John F.; Lin, Lanjia; Corsa, Amy; Gaggar, Anuj; Subramanian, G. Mani; et al. (Gastroenterology (New York, N.Y. 1943), 2014)
Little is known about the benefit of antiviral therapy for hepatitis B e antigen (HBeAg)−positive patients with high viral load and normal levels of alanine aminotransferase. We evaluated the effects of single and combination therapies in immune-tolerant patients with chronic hepatitis B. In a double-blind study, nucleos(t)ide-naïve patients with high levels of hepatitis B virus (HBV) DNA who were positive for HBeAg and had normal levels of alanine aminotransferase were randomly assigned to groups given either oral tenofovir disoproxil fumarate (TDF, 300 mg) and placebo (n = 64) or a combination of TDF (300 mg) and emtricitabine (200 mg, n = 62) for 192 weeks. The primary end point was proportion of patients with serum levels of HBV DNA <69 IU/mL at week 192. The study population (mean age was 33 years; 89% were Asian) was predominantly infected with HBV genotypes B and C (93%), 99% were HBeAg positive with a mean baseline level of HBV DNA of 8.41 log10 IU/mL. At week 192, 55% of patients (35 of 64) in the TDF+placebo group and 76% of patients (47 of 62) in the TDF+emtricitabine group had levels of HBV DNA <69 IU/mL (P = .016). No patients were found to have viral resistance to therapy. HBeAg seroconversion occurred in 3 patients (5%), all in the TDF+placebo group; no patient had loss of hepatitis B surface antigen. In multivariate analysis, female sex (odds ratio = 7.05; P = .002) and TDF+emtricitabine treatment (odds ratio = 3.9; P = .01) were associated with a favorable response. Both regimens were well tolerated. In HBeAg-positive patients with chronic HBV infection, high viral loads, normal levels of alanine aminotransferase, and therapy with the combination of TDF and emtricitabine provided better viral suppression than TDF alone, although rates of HBeAg seroconversion and hepatitis B surface antigen loss were low.